Cinobufotalin inhibits proliferation, migration and invasion in hepatocellular carcinoma by triggering NOX4/NLRP3/GSDMD-dependent pyroptosis - Liu, Chen; Wu, Jianmin; Li, Zhiwen; Huang, Xuanyu; Xie, Xianhe; Huang, Yun (Frontiers in Oncology, 2024)
IntroductionPyroptosis is an inflammatory form of programmed cell death that plays a significant role in tumorigenesis. Cinobufotalin (CB), a bufadienolide extracted from toad venom, is associated with antitumor effects in various cancers, including liver cancer. However, the role of CB in pyroptosis and its underlying mechanisms have not been well characterized.MethodsMTT, Colony formation, EdU, Wound healing and Transwell migration and invasion assays were applied to determine the effects of CB on the proliferation, migration, and invasion ability of hepatocellular carcinoma (HCC) cells in vitro. The subcutaneous xenograft mouse model and pulmonary metastasis model were used to evaluate the effect of CB on HCC cells in vivo. PCR, western blot, immunohistochemistry, immunofluorescence, and ELISA were used to verify the expression of proliferation, migration, pyroptosis, and inflammation related molecules after CB treatment. Using si-RNA and inhibitors to interfere with NOX4 and HLRP3 expression to validate the key signaling pathways of pyroptosis induced by CB treatment.ResultsIn vivo experiments using nude mice with xenografted HCC cells and in vitro experiments with HCC cell lines demonstrated that CB treatment significantly inhibited the proliferation, migration, and invasiveness of HCC cells. CB treatment also showed dose-dependent activation of the NLRP3 inflammasome complex in HCC cells, leading to gasdermin D-induced pyroptosis. However, these effects were abrogated via the pretreatment of HCC cells with VX-765, a caspase-1 inhibitor. Additionally, CB increased the production of reactive oxygen species (ROS) and H₂O₂, along with upregulating NOX4 protein expression in HCC cells. Conversely, NOX4 silencing or pretreatment with VAS2870 (an NOX4 inhibitor) or NAC (an ROS scavenger) suppressed the activation of the NLRP3 inflammasome complex and pyroptosis in CB-treated HCC cells.DiscussionOur study demonstrated that CB suppressed the proliferation, migration, and invasiveness of HCC cells by inducing pyroptosis through the activation of the NOX4/NLRP3/GSDMD signaling pathway. Therefore, our results suggest that CB is a promising therapeutic agent for HCC.